Exploring the perceptions of students on using Instagram as a digital portfolio - Haryo Guntoro Wicaksono; Henry Praherdhiono; Saidah Ulfa (Himpunan Pengembang Kurikulum Indonesia, 2026)
This study examines how students perceive and experience the use of social media as a digital portfolio in higher education. The main goal is to identify the advantages and disadvantages of using social media for digital portfolios, to highlight the challenges students face, and to examine its impact on teaching and learning in higher education. By filling research gaps, this study aims to reveal the benefits and drawbacks of using social media as a digital portfolio, the obstacles students encounter, and the effects on teaching and learning. This study employed a quantitative survey design to examine students' perceptions of social media use in their learning process. Social media has the potential to transform how students showcase their work and professional identity. It is crucial for educational institutions to support students in responsibly using social media as a digital portfolio, including educating them about online privacy and security. Faculty members can encourage responsible use of social media by integrating it into their teaching and evaluating students' online presence. While social media can help promote academic accomplishments, addressing privacy and ethical concerns is essential. Abstrak Studi ini mengeksplorasi bagaimana siswa memandang dan pengalaman menggunakan media sosial sebagai portofolio digital di pendidikan tinggi. Tujuan utamanya adalah untuk mengidentifikasi pro dan kontra menggunakan media sosial untuk portofolio digital, menyoroti tantangan yang dihadapi siswa, dan memeriksa dampaknya terhadap pengajaran dan pembelajaran di pendidikan tinggi. Dengan mengisi kesenjangan penelitian, penelitian ini bertujuan untuk mengungkapkan manfaat dan kerugian menggunakan media sosial sebagai portofolio digital, hambatan yang dihadapi siswa, dan efeknya pada pengajaran dan pembelajaran. Penelitian ini menggunakan metode kuantitatif dengan pendekatan survei untuk mengeksplorasi persepsi mahasiswa terhadap penggunaan media sosial dalam proses pembelajaran mereka. Media sosial memiliki potensi untuk mengubah cara siswa menampilkan karya dan identitas profesional mereka. Sangat penting bagi lembaga pendidikan untuk mendukung siswa dalam menggunakan media sosial secara bertanggung jawab sebagai portofolio digital, termasuk mendidik mereka tentang privasi dan keamanan online. Anggota fakultas dapat mendorong penggunaan media sosial yang bertanggung jawab dengan mengintegrasikannya ke dalam pengajaran mereka dan mengevaluasi kehadiran online siswa. Sementara media sosial dapat membantu mempromosikan prestasi akademik, mengatasi masalah privasi dan etika sangat penting. Kata Kunci: Instagram; media sosial; portofolio digital